(untitled) - The United nations development programme (UNDP) (New York, 2009)
This book addresses migration, a increasingly prominent issue in domestic and international debates. The book draws on the idea of the expansion of choice a concept which originates in the work of Nobel Laureate Amartya Sen. It provides a powerful lens and coherent framework through which to view current debates about migration. It proposes a bold vision to capture the large unrealized gains to human development from current and future mobility. It presents a range of evidence detailing significant positive impacts of mobility on human development, through such avenues as increased household incomes, and improved education and health indicators. The report will also explore where risks to human development arise when migration is a reaction to threats and denial of choice
Keywords: Emigration and immigration,Economic development,Di cư và nhập cư,Phát triển kinh tế